Producción de microcápsulas de almidón con aceite esencial de romero como potencial aplicación en la industria textil (2024)
The textile sector has enormous complexity due to the abundance of processes in which it participates, in addition to the great applicability of its products in sectors such as: clothing, home textiles, medicine, agriculture, etc. The characteristics of textiles such as a surface area, porous texture, and ability to retain moisture and heat, make them a favorable environment for the growth of microorganisms. Antimicrobial textiles have the capacity to prevent the proliferation of microorganisms in their fibers, their function is due to the microencapsulation of antimicrobial agents, which can be found in essential oils. The objective of this study was to develop starch microcapsules capable of storing and releasing rosemary essential oil, with the specific objectives of physicochemical characterization of the microcapsules and their release study in a solvent. Suspensions were prepared with different encapsulation techniques to synthesize the microcapsules. The suspensions were evaluated by laser diffraction analysis and spectrophotometry, evaluating particle size, stability over time, and oil release. The results reported that microcapsules without emulsifier showed faster release, while those stabilized with it maintained a more controlled release. Furthermore, it was observed that the average size of suspensions without Tween 80 remained constant, while suspensions containing it showed size variations. It was concluded that the SCT80 US suspension presents the best release conditions, thanks to its reduced release potential in petroleum ether and its encapsulation efficiency.